Intrinsic scaling for pde’s with an exponential nonlinearity - Henriques, Eurica (2006)
We consider strongly degenerate equations in divergence form of the type u_t − ∇ · (|u|^{γ(x,t)}∇u )= f , where the exponential nonlinearity satisfies the condition 0 < γ− ≤ γ(x, t) ≤ γ+. We show, by means of intrinsic scaling, that weak solutions are locally continuous.